Biostratigraphy and geochronology of the late Cenozoic of Córdoba Province (central Argentina) - Cruz, Laura Edith (2013)
In the last twenty years, several geological and stratigraphical studies have been undertaken in Córdoba Province, and they have provided useful bases for biostratigraphic work in the late Cenozoic. However, paleontological contributions have been limited to preliminary analyses of mammal assemblages, or specific discoveries. The aim of this work is to contribute to biostratigraphic knowledge of Argentina through the study of late Cenozoic mammals from Córdoba Province. Five localities have been analyzed: San Francisco, Miramar, Río Cuarto, Isla Verde, and Valle de Traslasierra. Through biostratigraphic analysis the first records of several taxa were established, and mammal assemblages with the description and correlation of the sedimentary strata were confirmed. Finally, three Assemblage Zones (Biozonas de Asociación) were proposed: 1) Neosclerocalyptus paskoensis-Equus (Amerhippus) assemblage zone with type area and profile based on the San Francisco locality, referred to the Lujanian (late Pleistocene-early Holocene), and comparable to the Equus (Amerhippus) neogeus Biozone of Buenos Aires Province; 2) Neosclerocalyptus ornatus-Catonyx tarijensis assemblage zone with type area and profile based on the San Francisco locality, referred to the Ensenadan (early Pleistocene) and comparable to the Mesotherium cristatum Biozone of Buenos Aires Province, and 3) Nonotherium hennigi-Propanochthus bullifer assemblage zone with type area and profile based on the Los Sauces river, Valle de Traslasierra, referred to the Montehermosan-Chapadmalalan interval (Pliocene), and comparable to the Trigodon gaudryi, Neocavia depressidens and/or Paraglyptodon chapadmalensis Biozones of Buenos Aires Province.